Avaliação da eficácia do tratamento da cessação do tabagismo iniciado durante internação hospitalar em pacientes com doença cardiológica ou respiratória agudizada - Garcia, Thaís [UNESP] (2015)
The aim of this study was to evaluate the smoking cessation rate in hospitalized patients with respiratory or cardiac disease who received smoking cessation intervention after one, three and six months of hospital discharge. We evaluated 227 hospitalized patients, 81 with acute respiratory diseases (59.7 ± 13.0 years) and 146 with cardiac disease (57.3 ± 17.1 years) regarding to smoking history, degree of motivation to quit smoking and intensity of nicotine dependence, anxiety and depression questionnaire, laboratory biochemical analysis and measurement of carbon monoxide in exhaled air. All patients received educational material about smoking cessation and pharmacological treatment to control withdrawal symptoms. The patients with respiratory disease returned in greater proportion in the ambulatory group for smoking cessation after discharge (14.9%) (p<0,001) and used more pharmacological treatment (35%) when compared to cardiac disease group (p=0.004). In relation to the total, 43,2% lost the follow-up and 14.5% of patients with respiratory diseases and 17.6% with cardiac diseases were abstinents (p=0.73) after one month. After three months, 11.4% (respiratory) and 10.6% (cardiac) were abstinents (p=0.86) and after six months, 11.9% of respiratory disease group and 12.8% of cardiac disease group were abstinents (p=0.62). The rate of smoking cessation in both groups was similar and the loss of patient follow-up for reassessment of the smoking status was high